Pengaruh Akuntabilitas, Kesesuaian Kompensasi, Pengendalian Internal, dan Budaya Organisasi terhadap Kecurangan Dana Desa - Elisa Putri Masni; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine the effect of accountability, compensation suitability, internal control, and organizational culture on village fund fraud. The population in this study were 55 villages in the City of Pariaman. The sampling method used is purposive sampling method. The sample criteria in this study are the Village Head, Village Secretary, and Village Treasurer from 55 villages in Pariaman City who directly participate in village financial management. The data is a primary data which collected by using questionnaires. The results of this study indicate that the suitability of compensation and Internal control have no effect on fraudulent village funds, while accountability and organizational culture have negative effects on village fund fraud.